2020
DOI: 10.1002/jtr.2344
|View full text |Cite
|
Sign up to set email alerts
|

Analysing domestic tourism flows at the provincial level in Spain by using spatial gravity models

Abstract: Domestic tourism represents a large share of the total tourism volume in Spain, but it is still an under‐researched topic. This study focuses on the determinants of domestic flows in Spain at provincial level. The prior assumption is that domestic tourism demand may be affected by specific local conditions that previous studies, mostly based on more aggregate data, would hardly capture. A gravity model and various spatial econometric models are estimated assuming alternative spatial weighting matrices. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 45 publications
8
23
0
1
Order By: Relevance
“…and Alvarez-Diaz et al (2020). The dummy variable for rainfalls (RAIN) is negative and significant, in line with prior expectations and the results ofLyons, Mayor, and Tol et al (2009) andAlvarez-Diaz et al (2020).…”
supporting
confidence: 87%
See 2 more Smart Citations
“…and Alvarez-Diaz et al (2020). The dummy variable for rainfalls (RAIN) is negative and significant, in line with prior expectations and the results ofLyons, Mayor, and Tol et al (2009) andAlvarez-Diaz et al (2020).…”
supporting
confidence: 87%
“…The log-likelihood at convergence and the Akaike information criterion (AIC) indicate that the RPLc-ECM model provides a better fit. Accordingly, the discussion of results that follows is based on this model.As expected, DIST exerts (on average) a negative effect on tourists' utility, in line withLyons et al (2009),Chandra et al (2014), De Valck et al (2017 andGosens and Rouwendal (2018),Pompili et al (2019) andAlvarez-Diaz et al (2020), among others. The spread parameter (standard deviation of the random component)…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Technological innovation 13 and knowledge spillovers 14 cannot be ignored in driving tourism productivity and making tourism demand grow. Alvarez‐Diaz et al 15 , Marrocu and Paci 16 , Massidda and Etzo 9 confirmed that the size of the population is also one of the drivers of tourism demand. Despite the large number of studies exploring the factors affecting tourism demand, most researchers have focused more on the impact of single aspects of socio-economic or natural factors on tourism demand, and there are no studies based on a geographic perspective that integrate the various dominant factors into a comprehensive mechanism of impact on tourism demand.…”
Section: Introductionmentioning
confidence: 91%
“…A series of studies have indicated spatial spillover effects of domestic tourism development in many countries, such as Italy [26], Spain [27], and Korea [28]. In China, Yang and Fik [29] recognize the positive spatial spillover effects in domestic tourism's growth rate.…”
Section: Spatial Effectsmentioning
confidence: 99%